Vertical Product Differentiation, Market Entry, and Welfare - Markus Reisinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This paper analyses a model of vertical product differentiation with one incumbent and one entrant firm. It is shown that if firms can produce only one quality level welfare in this entry game can be lower than in monopoly. This is the case if qualities are strategic complements because the incumbent may distort its quality downwards. If firms can produce a quality range and practice non-linear pricing welfare in case of entry deterrence is higher than in monopoly because the incumbent enlarges its product line. If entry is accommodated consumer rent increases but the consequences on welfare are ambiguous.
urn:nbn:de:bvb:19-epub-479-5
Keywords: D43; L13; L65; 330; Entry Deterrence; Price Discrimination; Vertical Differentiation